Survey research implementation in educational centers in Chile: fulfillments of ethical and legal regulatory aspects - Merino-Osorio, Catalina; Mattar T., Gustavo; Leppe Z., Jaime; Bahamondes M., Paz; Lecaros, Juan Alberto (Acta Bioethica, 2017)
Background: Research in educational centers is a frequent source of social and health related studies. Objective: To determine the knowledge and adherence to the current legal and ethical regulations to research performed on children at educational institutions. Methodology: Cross-sectional study online survey-type. The level of knowledge and adherence to the ethical regulation and legislation in Chile, to conduct research with minors was consulted. Results: 126 educational institutions responded the survey; 69% belonged to urban centers; 60% corresponded to those under the Municipality umbrella and 34% to charter schools. Research was performed in 31,8% of the consulted institutions, 41% of the research was on health issues and 30,8% on education. The 27,5% answered that they had the approval of ethical-scientific committee, 82% answered that they neither received nor had any awareness of regulatory aspects on research. Conclusion: There is low knowledge and adherence to ethical and legal regulation to research performed with children in educational centers. A journey for dissemination of results was performed and a flow chart was created by experts and proposed to the school directors to contribute to the adherence of ethical and regulatory aspects of research in educational centers.